The potential of conservation-restoration documentation as a source of information for the library catalogue (Libellarium: journal for research in the field of information and related sciences, 2024)
Purpose. The aim of the paper is to demonstrate how conservation-restoration documentation can enhance the volume and value of information provided in library catalogues. Conservation-restoration documentation can be a valuable source of information, providing data on the condition, history and preservation of materials. The availability of this information promotes transparency and commitment to the care of cultural heritage.Approach/methodology/design. The research includes an analysis of the legal framework, code of ethics, and guidelines to demonstrate the responsibility of professionals involved in the protection of cultural heritage. In addition, the paper traces the historical development of conservation-restoration documentation, from its early written forms to its integration with modern technologies. It highlights the activities of the Preservation and Storage Department of the National and University Library in Zagreb including the structure and ongoing development of its documentation database.Findings. The paper addresses the frequent disparity between the variety of dana offered to users through library catalogues and the broader range of information available in smaller databases used in daily library operations. Integrating this additional data into catalogues fosters user trust and affirms the library’s role in preserving cultural heritage as a fundamental objective.Originality/value. The paper presents the knowledge gained through many years of work on conservation-restoration documentation and the potential of available data for library catalogues and similar systems. Although such documentation may occasionally contain sensitive information, there are no significant practical obstacles that would prevent this documentation from being used as a source of information for the library catalogues. For users and researchers, the library catalogue remains the primary source of information about library materials. Considering the value of the materials kept in the Special Collections Departments of the National and University Library in Zagreb and the special attention given to their preservation, the originality and value of the resulting conservation-restoration documentation are indisputable.
Keywords: conservation and restoration documentation; cataloguing; National and University Library in Zagreb; metadata